Motivation and Challenges Facing Employers in Recruiting Professional Women in Building Construction Companies in Dar-Es-Salaam, Tanzania - Morin N. Nalitolela; Shubira L. Kalugila; Mercy B. Muganyizi; Dennis N.G.A.K. Tesha (International Journal of Engineering and Management Research, 2020)
The study intended to assess the motivation and challenges facing employers in recruitment of professional women in building construction companies; by analyzing motivation; examining the challenges encountered; and proposing the possible measures to overcome challenges facing employers in recruiting professional women in building construction companies, in Dar-Es-Salaam, Tanzania. This descriptive designed survey study, engaged large size contractors as a unit of analysis, with building contractors from Class I and II, within Dar-Es-Salaam Tanzania, as a study population and a sample. Moreover, the study involved non-probability sampling; specifically, judgmental sampling, which was used in determining the number of registered building construction firms in Dar-Es-Salaam particularly from Class I and II. Literature review; open and closed ended questionnaires administered to employers and human resources managers in building construction companies in Dar-Es-Salaam, were used in collecting primary and secondary qualitative and quantitative data. In collecting data, total of 56 questionnaire were distributed, whereby only 41 (73%) were returned. Quantitative data were analyzed using Statistical Package for Social Sciences (SPSS), while qualitative data were analyzed thematically. Findings revealed the need to address gender balance; non-discriminatory policy; improved staff retention (you can keep your employees, boost their morale); a better reflection to the customers or clients; encourage organization to change from gender stereotype; different perspective (benefits from different points of view and approaches); enhance collaboration (improve team processed and group collaboration); the perception of women being more multitasked than men, and the need to explore a wide talent pool; women are professionally ethical, committed to their work, and less corrupt, with better listening and soft skills; improve reputation (no gender biasness to your company); and women are loyal, practical innovative, and patience, as the most prevalent motivations that; pushes employers to recruit professional women in building construction companies. Furthermore, the critical challenges revealed were; work-life balance, private life demands, emotions, and non-family friendly working hours; lack of good recruitment practises, procedures and selection plans; lack of good staff development plan; lack of gender policy; lack of confidence and low number of female applicants in the building construction industry; and lack of proper motivation and mentorship policy. The study concluded that; more attention must be made on recruiting more women in building construction industry as a part of the gender equality, in order to increase their participation number in the construction industry, against male, alongside addressing all the challenges and motivation factors revealed in the study. Lastly, the study recommended; incentives (such as training and mentoring); support and encouragement of women participation in construction; enhancement of labour laws and regulations; and mandatory to recruitment of more women in construction industry.